Penerapan Pembelajaran Tari Kreasi untuk Siswa SD dalam Mengembangkan Kreativitas Mahasiswa Jurusan Pendidikan Seni Pertunjukan STKIP Muhammadiyah OKU Timur - Chandra, Dendy; Julta, Arbi (LPPPI Publishing, 2025)
Students majoring in Performing Arts Education Concentration in Dance as a prospective art teacher must have competencies that support all fields, including the creation of dance at the level of early childhood. Art competencies for students given theoretical and practical experience can be given at the Education Dance Course. The aim of the course is to improve the competence of students in terms of knowledge and understanding in the field of dance, problem solving skills, critical and democratic thinking, respect for art and cultural diversity and the enjoyment of art, creativity and appreciation in dance, and cooperation in group, and able to create dance for early childhood. In their lectures, students are required to be able to express, be creative and create art. One of the students' creative skills is creating dances for children which will later be applied to children. This is given as a provision for aesthetic experiences for students and children of course, because at the end of the lecture students will make a dance performance involving children in early childhood or kindergarten.